Factors affecting hospital services overutilization and reductive strategies in Iran: a qualitative study to explore experts' views. Issue 5 (20th October 2022) - Doshmangir, Leila; Jabbari, Hossein; Arab-Zozani, Morteza; Naghavi-Behzad, Mohammad; Abedi, Zeinab; Mostafavi, Hakimeh
ABSTRACT: Objectives: This study aimed to investigate the viewpoints of the main stakeholders of the Iranian healthcare system about the overutilization of hospital services and strategies to eliminate or reduce it in Iran. Methods: This is a qualitative study and thematic data analysis using face-to-face semi-structured interviews and Focus Group Discussions (FGDs). We conducted eight interviewers and two FGDs with hospital stakeholders including faculty members, insurance organizations' authorities, experienced hospital administrative staff, hospital managers, and health-care providers. Results: The factors leading to the overutilization of hospital services were categorized into four main themes including site of service, quality, supplier push, and demand pull. Strategies for eliminating or reducing the overutilization of hospital services are also identified based on the influential factors. Conclusion: Addressing overutilization of hospital services in the health system and adherence to policies for reducing or eliminating overutilization is a way to make preventive strategies to overcome overutilization. Developing a national plan to integrate utilization management into health system programs is a strategy to combat overutilization in various levels of the health system including hospital setting.